Students’ Engagement in Learning Recount Text through TikTok-Based Projects: A Senior High School Case Study - Salsabila Tazkia; Zulfi Zumala Dwi Andriani (English Language Education, Universitas Internasional Batam, 2026)
This study investigated students’ engagement in learning recount texts through TikTok-based projects at the senior high school level. It aimed to explore how TikTok-based projects influenced students’ behavioral, cognitive, and emotional engagement during the learning process. This research employed a qualitative case study design involving 36 tenth-grade students and one English teacher selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. To ensure trustworthiness, source, method, and theoretical triangulation were applied. The findings revealed that TikTok-based projects enhanced students’ engagement in learning recount texts. Students actively participated in group discussions, script writing, pronunciation practice, and video production, demonstrating strong behavioral engagement. They also showed cognitive engagement through organizing events chronologically, revising scripts, and improving language accuracy, while emotional engagement was reflected in increased confidence, enjoyment, and motivation. The familiarity of TikTok and its creative features encouraged students’ active involvement in the learning process. Although some students initially experienced challenges related to grammar, video editing, and speaking in front of the camera, these difficulties were gradually overcome through peer collaboration and teacher support. In conclusion, TikTok-based projects provide an effective and student-centered approach to promoting student engagement in English language learning.